Sogni e visioni di madri: tra tradizione classica e innovazione cristiana - Franchi, Roberta (Augustinianum, 2020)
Following the example of classical literature, Christian texts of the fourth century portray dreams of pregnant mothers. In such dreams, the mother sees her son or daughter, and knows the name of the infant and the great future for which the infant is destined. The dreams of Emmelia, Nonna and Monica are described in the writings of their sons (Gregory of Nyssa, Gregory of Nazianzus and Augustine, respectively). Thanks to her visions and dreams about her child, each mother becomes a mediatrix of God.